El contrato de relevo. Los verdaderos efectos de creación y mantenimiento del empleo derivados de la jubilación parcial en el ordenamiento español - Crisanto Castañeda, Ana Cecilia (Revista de Derecho, 2019)
The present investigation conducts a juridical-critical analysis on the labour regime of release contract, institution liked to partial retirement by the Spanish lawmaker with the explicit objective of creating and/or maintaining work in companies. Beyond the concrete issues of interpretation of the norms involved what calls the attention the most about the partial retirement regime and the release contract are the dysfunctions between these two figures, which at the same time is an evidence of the true effects they have on work policy in the productive organization and on work markets in general.
Keywords: Partial retirement; release contract; work policy; unemployment; work distribution